Economic Instruments for Reducing CO2 Emmissions and their Consequences - Renata Slabe Erker; Klemen Koman; Boris Majcen (Central European Public Administration Review)
This contribution is an economic evaluation of various combinations of economic instruments for reducing CO2 emissions. The evaluation of effects linked to the achievement of Kyoto and post-Kyoto goals was developed by using the GEME3 general equilibrium model as developed within the framework of the 5. and 6. EU OP (project ENG2-CT- 1999-00002). We are calculating the effects of varying environmental policies for Slovenia based on variations in key macroeconomical markers. The most important finding is, that the loss of competitive advantages for Slovenia due to enforced environmental protection measures is not sizeable. The most favorable scenario in macroeconomic terms is the scenario of emissions trading in energy intensive sectors with a gradual transition to auctioning and carbon taxation in other sectors, whereby the tax revenues are returned to reduce the rate of social security contributions.